2022
DOI: 10.1007/s10508-021-02265-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Relationships Pre- and Early- COVID-19 Pandemic: Findings from a Probability Sample of U.S. Undergraduate Students

Abstract: In the wake of the COVID-19 pandemic, most U.S. colleges closed their campuses—including residence halls—causing significant disruption to students’ lives. Two waves of data were collected from undergraduate students enrolled at a large U.S. Midwestern university: Wave 1 was a confidential online survey of 4989 randomly sampled undergraduate students collected in January/February 2020; Wave 2 was collected in April/May 2020 following campus closure. Our research aimed to: (1) assess how the COVID-19 related ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
3
33
1
Order By: Relevance
“…Researchers have primarily evaluated social stress and academic stress ( Vidal Bustamante et al, 2022 ), anxiety ( Brooks et al, 2020 ; Kochuvilayil et al, 2021 ; Bountress et al, 2022 ; Kaur et al, 2022 ; Song et al, 2022 ; Tshering and Dema, 2022 ), anger ( Brooks et al, 2020 ), and depression ( Brooks et al, 2020 ; Bountress et al, 2022 ; Tshering and Dema, 2022 ) in this vulnerable population. In addition, a plethora of other reported outcomes during COVID-19 included loneliness ( Xiang et al, 2020 ; Kaur et al, 2022 ), isolation ( Hasratian et al, 2021 ; Kaur et al, 2022 ), sleep disturbance/difficulty sleeping or insomnia ( Kochuvilayil et al, 2021 ; Zhang et al, 2021 ; Song et al, 2022 ), fatigue ( Mosleh et al, 2022 ), burnout ( Kaggwa et al, 2021 ), PTSD ( Brooks et al, 2020 ; Bountress et al, 2022 ), future uncertainty ( Miconi et al, 2022 ), witnessing death in relatives ( Hasratian et al, 2021 ), relocation/displacement ( Hasratian et al, 2021 ), alcohol ( Bountress et al, 2022 ), e-cigarette ( Merianos et al, 2022 ), and cannabis use ( Merianos et al, 2022 ; Merrill et al, 2022 ), financial insecurities, loss or stressors of income ( Hasratian et al, 2021 ), unhealthy eating behaviors ( Kochuvilayil et al, 2021 ), academic concerns ( Kochuvilayil et al, 2021 ; Vidal Bustamante et al, 2022 ), contagion (i.e., fear of contracting the disease; Wheaton et al, 2021 ), mobile phone addiction ( Jiang et al, 2022 ; Peng et al, 2022 ), relationship problems ( Gallegos et al, 2021 ; Herbenick et al, 2022 ), sexual activity problems ( Ellakany et al, 2022 ; Herbenick et al, 2022 ), increased screen time ( Ellakany et al, 2022 ), suicidal behavior ( López Steinmetz et al, 2021 ; Bountress et al, 2022 ; Rahman et al, 2022 ), self-harm ( Kim et al, 2021 ), and fear of death ( Xiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have primarily evaluated social stress and academic stress ( Vidal Bustamante et al, 2022 ), anxiety ( Brooks et al, 2020 ; Kochuvilayil et al, 2021 ; Bountress et al, 2022 ; Kaur et al, 2022 ; Song et al, 2022 ; Tshering and Dema, 2022 ), anger ( Brooks et al, 2020 ), and depression ( Brooks et al, 2020 ; Bountress et al, 2022 ; Tshering and Dema, 2022 ) in this vulnerable population. In addition, a plethora of other reported outcomes during COVID-19 included loneliness ( Xiang et al, 2020 ; Kaur et al, 2022 ), isolation ( Hasratian et al, 2021 ; Kaur et al, 2022 ), sleep disturbance/difficulty sleeping or insomnia ( Kochuvilayil et al, 2021 ; Zhang et al, 2021 ; Song et al, 2022 ), fatigue ( Mosleh et al, 2022 ), burnout ( Kaggwa et al, 2021 ), PTSD ( Brooks et al, 2020 ; Bountress et al, 2022 ), future uncertainty ( Miconi et al, 2022 ), witnessing death in relatives ( Hasratian et al, 2021 ), relocation/displacement ( Hasratian et al, 2021 ), alcohol ( Bountress et al, 2022 ), e-cigarette ( Merianos et al, 2022 ), and cannabis use ( Merianos et al, 2022 ; Merrill et al, 2022 ), financial insecurities, loss or stressors of income ( Hasratian et al, 2021 ), unhealthy eating behaviors ( Kochuvilayil et al, 2021 ), academic concerns ( Kochuvilayil et al, 2021 ; Vidal Bustamante et al, 2022 ), contagion (i.e., fear of contracting the disease; Wheaton et al, 2021 ), mobile phone addiction ( Jiang et al, 2022 ; Peng et al, 2022 ), relationship problems ( Gallegos et al, 2021 ; Herbenick et al, 2022 ), sexual activity problems ( Ellakany et al, 2022 ; Herbenick et al, 2022 ), increased screen time ( Ellakany et al, 2022 ), suicidal behavior ( López Steinmetz et al, 2021 ; Bountress et al, 2022 ; Rahman et al, 2022 ), self-harm ( Kim et al, 2021 ), and fear of death ( Xiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the COVID-19 pandemic presents new and unique challenges that the United States has not faced before. For example, in a study comparing outcomes for students in the United States prior to the pandemic closures (January/February 2020) and post-pandemic closures (April/May 2020), 2.6% of students reported living at home before the pandemic and 71% reported living at home after the pandemic began and universities closed (Herbenick et al, 2022 ). This information indicates a significant shift in the lives of college students due to the pandemic and some researchers believe that they may be a unique population experiencing these shifts in living situations compared to older, more professionally established adults (Herbenick et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a decrease in desire, arousal, lubrication, orgasm, and sexual satisfaction amongst Polish and Italian adult women (most in romantic relationships) in response to the COVID-19 pandemic (Fuchs et al, 2020 ; Schiavi et al, 2020 ). The pandemic is associated with changes in romantic and sexual relationships with decreased sexual behavior, increased conflict, and increased break-ups or partner separation for those in relationships (Herbenick et al, 2022 ; Luetke et al, 2020 ). It has also been reported that sexually active individuals experienced lower levels of depression and anxiety during the COVID-19 pandemic compared to individuals who were not sexually active, indicating potential positive benefits of sexual activity (Mollaioli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next set of papers examined the influence of the COVID-19 pandemic on sexual relationships. Herbenick et al ( 2022 ) conducted an online survey of college students at a large Midwestern university in the USA both before and after campus closed due to the pandemic. They found many sexual behaviors remained unchanged but participation in oral, vaginal, and anal sex significantly decreased over time.…”
mentioning
confidence: 99%